Functionalized gold nanoparticles for the binding, stabilization, and delivery of therapeutic DNA, RNA, and other biological macromolecules - Robert K DeLong (Dove Medical Press, 2010)
Robert K DeLong1, Christopher M Reynolds1, Yaneika Malcolm1, Ashley Schaeffer1, Tiffany Severs2, Adam Wanekaya21Department of Biomedical Science (Cell and Molecular Biology Program), 2Department of Chemistry, Missouri State University, Springfield, MO, USAAbstract: Nanotechnology has virtually exploded in the last few years with seemingly limitless opportunity across all segments of our society. If gene and RNA therapy are to ever realize their full potential, there is a great need for nanomaterials that can bind, stabilize, and deliver these macromolecular nucleic acids into human cells and tissues. Many researchers have turned to gold nanomaterials, as gold is thought to be relatively well tolerated in humans and provides an inert material upon which nucleic acids can attach. Here, we review the various strategies for associating macromolecular nucleic acids to the surface of gold nanoparticles (GNPs), the characterization chemistries involved, and the potential advantages of GNPs in terms of stabilization and delivery.Keywords: gold, nanoparticles, nanomaterials, RNA, nucleic acid